KONTRIBUSI DAN MOTIVASI PEKERJA WANITA DALAM MENINGKATKAN EKONOMI KELUARGA - Dadang Sudirman (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2016)
The role of women in development is continually reinforced in every aspect of life. Women currently have the equal opportunities in education that the number of educated women has been increasing significantly. Therefore, the fields of employment have also been more widely available for women. It is likely for women who have been working since their early age will eventually continue working despite being married. As housewives they will keep on working based on various motivations such as the need for self-actualization or the need for contributing in their household economy. The objectives of this study were to find out (a) The amount of revenue contribution of the working wives to family income (b) Motivations of housewives who choose to work. Moreover, the study brought out the following results (a) Based on the contributions of each respondents to their family income, the average contribution of the working wives was up to 46,1% of the total family income (b) All respondents were housewives in their productive ages with the average respondents were 44 year olds. The majority of respondents were high school graduates, and the rest had diploma and bachelor degree. (c) The motivations of the respondents to work were mainly to increase their family income, social status, and  avoid any dependence on their spouses.